ANALISIS KEMAMPUAN LITERASI NUMERASI SISWA SMA PADA PEMBELAJARAN MATEMATIKA - Harisah, Zulkirah; Aryani, Irma; Rahmi, Rahmi; Musriandi, Riki; Hasanah, Hasanah (Jurnal Dedikasi Pendidikan, 2025)
This research aims to describe students' numeracy literacy skills in class X mathematics learning at SMAN 1 Kuta Baro. The type of research used is qualitative with a descriptive approach. The subjects in this research were class X students of SMAN 1 Kuta Baro. The subject selection was based on the test results given to 39 students. From the test results, 6 students were selected as subjects with 2 students in the high category, 2 students in the medium category, and 2 students in the low category. Data collection techniques used numeracy literacy tests and interview results. The data analysis technique used is to give a score to each subject's answer. The score is determined according to the numeracy literacy indicators, namely: 1) Able to use various kinds of numbers or symbols related to basic mathematics in solving daily life problems; 2) Able to analyze information displayed in various forms (graphs, tables, charts, diagrams, etc.); 3) Able to interpret analysis results to predict and make decisions. The results of this research show that 7.40% of students are in the high category, 44% are in the medium category, and 48% are in the low category, so it can be concluded that in general students' ability to solve numeracy literacy questions is still low